Q fever endocarditis: a diagnostic challenge in a complex cardiological case - Riccardo Rovelli; Elisa Brangi; Francesca Capasso; Martina Mazzini; Michela Raffo; Enrico Vizzardi (Monaldi Archives for Chest Disease)
Q fever endocarditis remains a diagnostic challenge today. Although it is a rare condition, it is crucial to recognize, as it represents the most common cause of endocarditis with persistently negative blood cultures. Here, we present the case of a 73-year-old woman with a history of coronary artery disease and systemic sclerosis who was admitted to the hospital complaining of asthenia and dyspnea. An echocardiographic examination revealed a highly mobile pedunculated mass on the mitral valve, suggestive of endocarditis. During the diagnostic workup, blood cultures were repeatedly negative, but serological testing confirmed positivity for Coxiella burnetii (IgG phase I 1:128). After diagnosing Q fever endocarditis, antibiotic therapy with doxycycline and hydroxychloroquine was initiated but was soon discontinued due to the development of renal impairment and thrombocytopenia. The clinical course was further complicated by cardiac arrest, leading to the patient's death. Given the rarity of this condition, this case highlights the importance of considering Q fever endocarditis in the differential diagnosis of blood culture-negative endocarditis and underscores the need for rapid diagnosis using advanced diagnostic techniques to improve patient outcomes.